NILAI-NILAI SUFISTIK DAN NILAI-NILAI PEDAGOGIK TRANSFORMATIF DALAM NOVEL SYAIKH SITI JENAR KARYA AGUS SUNYOTO: STUDI STRUKTURALISME GENETIK - Riadi, Sugeng (Prosiding Seminar Nasional Berseri, 2017)
MysticalÂ And Transformative Pedagogic Values In Syaikh Siti Jenar Novel By Agus Sunyoto: Genetic Structuralism.This research aims to know and understand more deeply about mystical values and transformative pedagogic values in the Syaikh Siti Jenar novel written by Agus Sunyoto. The method appliedin this studyis acontent analys is approach using genetic structure by Lucien Goldmann. The focus of this study was the intrinsic and extrinsic structure of meaningin the novel. Moreover, the subfocuses of this study were (1) The structure (plot, characters, setting, andtheme) builtin Syaikh Siti Jenarnovel; (2) The social structure are builtin Syaikh Siti Jenarnovel; (3) The mystical values contained in the Syaikh Siti Jenar novel; (4) The transformative pedagogical values containedin the Syaikh Siti Jenar novel; and (5) The world view of the author of the Syaikh Siti Jenar Novel.The results of the study show a number of mystical values and transformative pedagogic values. Mystical values include: repentance, ascetic, indigent, patience, gratitude, pleasure, and trust. While the transformative pedagogic values includealtruism, egalitarian, pluralism, andeclectic. The findings of the author’sworld view includes figures deconstruction of the teachings of Syaikh Siti Jenar, cultural missionary endeavor, the concept of super human, mystical literature, and literary history.